The effect of obesity and type 1 diabetes on renal function in children and adolescents. Issue 6 (11th August 2014) - Franchini, Simone; Savino, Alessandra; Marcovecchio, M Loredana; Tumini, Stefano; Chiarelli, Francesco; Mohn, Angelika
Abstract Background Early signs of renal complications can be common in youths with type 1 diabetes (T1D). Recently, there has been an increasing interest in potential renal complications associated with obesity, paralleling the epidemics of this condition, although there are limited data in children. Hypothesis Obese children and adolescents present signs of early alterations in renal function similar to non‐obese peers with T1D. Subjects Eighty‐three obese (age: 11.6 ± 3.0 yr), 164 non‐obese T1D (age: 12.4 ± 3.2 yr), and 71 non‐obese control (age: 12.3 ± 3.2 yr) children and adolescents were enrolled in the study. Methods Anthropometric parameters and blood pressure were measured. Renal function was assessed by albumin excretion rate (AER), serum cystatin C, creatinine and estimated glomerular filtration rate (e‐GFR), calculated using the Bouvet's formula. Results Obese and non‐obese T1D youths had similar AER [8.9(5.9–10.8) vs. 8.7(5.9–13.1) µg/min] and e‐GFR levels (114.8 ± 19.6 vs. 113.4 ± 19.1 mL/min), which were higher than in controls [AER: 8.1(5.9–8.7) µg/min, e‐GFR: 104.7 ± 18.9 mL/min]. Prevalence of microalbuminuria and hyperfiltration was similar between obese and T1D youths and higher than their control peers (6.0 vs. 8.0 vs. 0%, p = 0.02; 15.9 vs. 15.9 vs. 4.3%, p = 0.03, respectively). Body mass index (BMI) z‐score was independently related to e‐GFR (r = 0.328; p < 0.001), and AER (r = 0.138; p = 0.017). Hemoglobin A1c (HbA1c) correlated with AER (r = 0.148; p = 0.007) but not with eGFR (r = 0.041; p = 0.310). Conclusions Obese children and adolescents show early alterations in renal function, compared to normal weight peers, and they have similar renal profiles than age‐matched peers with T1D.